Cumulative risk assessment in unstable angina: clinical, electrocardiographic, autonomic, and biochemical markers. Issue 1 (1st January 2003) - Kennon, S; Price, C P; Mills, P G; MacCallum, P K; Cooper, J; Hooper, J; Clarke, H; Timmis, A D
Abstract : Objectives: To determine the incremental value of clinical data, troponin T, ST segment monitoring, and heart rate variability for predicting outcome in patients with non-ST elevation acute coronary syndromes. Methods: Prospective cohort study of 304 consecutive patients. Baseline clinical and electrocardiographic data were recorded, serial blood samples were obtained for troponin T assay, and 48 hour Holter monitoring was performed for ST segment and heart rate variability analysis. End points were cardiac death and non-fatal myocardial infarction during 12 months' follow up. Results: After 12 months, 7 patients had died and 21 had had non-fatal myocardial infarction. The risk of an event was increased by troponin T > 0.1 μg/l, T wave inversion on the presenting ECG, Holter ST shift, and a decrease in the standard deviation of 5 minute mean RR intervals. Positive predictive values of individual multivariate risk were low; however, analysis of all multivariate risk markers permitted calculation of a cumulative risk score, which increased the positive predictive value to 46.9% while retaining a negative predictive value of 96.9%. Conclusion: A cumulative approach to risk stratification in non-ST elevation coronary syndromes successfully identifies a group in whom the risk of cardiac death or non-fatal myocardial infarction approaches 50%.